2022
DOI: 10.3389/fonc.2022.1037145
|View full text |Cite
|
Sign up to set email alerts
|

Global research status and frontiers on microvascular invasion of hepatocellular carcinoma: A bibliometric and visualized analysis

Abstract: IntroductionOver the past decade, several studies on the microvascular invasion (MVI) of hepatocellular carcinoma (HCC) have been published. However, they have not quantitatively analyzed the remarkable impact of MVI. Therefore, a more comprehensive understanding of the field is now needed. This study aims to analyze the evolution of HCC-MVI research and to systematically evaluate the scientific outputs using bibliometric citation analysis.MethodsA systematic search was conducted on the Web of Science Core Col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Despite a thorough analysis, we were unable to demonstrate a significant impact of D-HOPE on HCC recurrence. In our series, HCC recurrence was closely associated with HCC features, such as microvascular invasion and tumor grading, which is consistent with the evidence from the literature [ 82 , 83 ]. In contrast with the findings from the Zurich group [ 55 ], even after adjusting for potential confounders, we did not observe any significant differences in HCC recurrence rate between recipients of a D-HOPE-treated graft and those who received a graft preserved by SCS.…”
Section: Discussionsupporting
confidence: 92%
“…Despite a thorough analysis, we were unable to demonstrate a significant impact of D-HOPE on HCC recurrence. In our series, HCC recurrence was closely associated with HCC features, such as microvascular invasion and tumor grading, which is consistent with the evidence from the literature [ 82 , 83 ]. In contrast with the findings from the Zurich group [ 55 ], even after adjusting for potential confounders, we did not observe any significant differences in HCC recurrence rate between recipients of a D-HOPE-treated graft and those who received a graft preserved by SCS.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have established that the presence of MVI is one of the key factors in early recurrence of HCC and poor outcomes after curative liver resection or liver transplantation. 13 Preoperative assessment of MVI is important for accurate selection of candidates for the various treatment options. For example, studies in which MVI status was evaluated preoperatively found that the rate of early recurrence was lower after surgical resection than after radiofrequency ablation and that anatomical resection was superior to nonanatomical resection.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have established that the presence of MVI is one of the key factors in early recurrence of HCC and poor outcomes after curative liver resection or liver transplantation. 13 Preoperative assessment of MVI is important for accurate selection of candidates for the various treatment options. For example, studies in which MVI status was…”
Section: Discussionmentioning
confidence: 99%
“…RMI based on ultrasonography, menopausal status, and serum CA125 levels can quantitatively assess the risk of malignancy for accurate preoperative diagnosis of OC ( 25 ). Analyzing keyword bursts can help researchers in identifying the frontier or future trends in specific fields ( 35 ). The keyword with the highest burst intensity is pelvic masses, spanning from 2007 to 2012.…”
Section: Discussionmentioning
confidence: 99%